Not in‐sourced here! When does external technology sourcing yield familiar versus novel solutions? - Klueter, Thomas; Ghosh, Anindya; Rosenkopf, Lori (Strategic Management Journal, 2025)
Abstract Research Summary When established firms source technology from specialized technology firms, extant research has typically assumed that this in‐sourced technology is novel . We test this assumption by modeling in‐sourcing decisions using a problem‐solution lens wherein firms choose from available external technological solutions to solve their market problems. Since the locus of identification, evaluation, and selection of external solutions remains internal to the firm's R&D personnel, we argue that they frequently prefer familiar over novel solutions. We identify two factors that help firms overcome this preference for familiarity: when top managers focus their attention on the market problem or when they receive feedback from unexpected failures to solve that problem. Our case control analysis of 715 in‐sourced emerging technological solutions in the biopharmaceutical industry offers broad support to our theoretical framework. Managerial Summary Established firms are commonly advised to source novel technologies externally. Yet since this sourcing process is driven by in‐house R&D personnel, we suggest that a firm's choice of external technology solutions may still tend toward familiar ones. We confirm this preference by examining in‐sourcing events of emerging technological solutions by established firms in the biopharmaceutical industry. Despite this preference, we then show that increased top management attention toward a market problem and experiencing unexpected failures in bringing products to market catalyze a receptiveness to novel technological solutions. Our findings help managers in established firms recognize that their claims or intentions to seek novel technology are not always consistent with actual in‐sourcing choices, and suggest when firms can overcome this tendency.